BASELINE BODY COMPOSITION OF OBESE INDIVIDUALS ACCORDING TO DIABETES STATUS IN MALAYSIA - Abidin, Nur Azlin Zainal; Mohkiar, Farah Huda; Zamri, Liyana Ahmad; Tan, You Zhuan; Mansor, Fazliana; Tsen, Poh Yue; Lim, Shu Yu; Tikfu, Gee (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Measurement of human body composition plays an important role in characterizing health status, as well monitoring treatment or intervention outcomes especially in individuals with obesity. In Malaysia, however, there is insufficient evidence of body composition among obesity with and without diabetes. This study aimed to describe the baseline body composition of obese individuals according to their diabetes status. METHODOLOGY This is the baseline data of a multicentre intervention study involving obese patients undergoing metabolic surgery in Malaysia. Patients were recruited from obesity clinics and weight management centres. Patients with a body mass index (BMI) ≥25 kg/m2 were categorized into 3 groups: non-diabetes, prediabetes, and diabetes. Body composition components including skeletal muscle mass (SMM), body fat mass (BFM), percentage body fat (PBF) and visceral fat area (VFA) were measured using a bioimpedance analyzer (Inbody S10). Statistical analysis was done using SPSS version 28. RESULT A total of 75 patients were included in this baseline recruitment. Most participants were female (n=69.3%), with an overall mean age of 37.8 (± 8.1) years. In view of major ethnicity distribution, majority of the patients are Malay (65.3%), followed by Chinese (10.7%) and Indian (10.7%). The median BMI was 38.1 kg/m2 (IQR: 32.7–49.3 kg/m2). There is a significant difference in SMM, BFM, PBF and VFA between patients without diabetes and prediabetes (p<0.05). Similarly, there was a significant difference in parameters above between patients without diabetes, and those with diabetes (p<0.05). However, no significant difference was observed between prediabetes and diabetes group. CASE Our baseline data showed there was a significant difference in body composition between obese patients with diabetes and obese patients without diabetes. It is important to investigate how metabolic surgery may influence the changes in body composition according to the diabetes risk among obese patients.